Comparison of the synthesis of the alpha-amylase enzyme by the native strain Bacillus licheniformis in immobilized and immersed cells - Fahimeh Mahmoudnia (Iranian Journal of Microbiology)
Background and Objectives: The study focused on the amylase enzyme, widely used in the industrial starch liquefaction process. We looked into the best way to immobilize the native strain Bacillus licheniformis, which is the only alpha-amylase-producing bacterium, by trapping it in calcium alginate gel. This is a promising way to increase enzyme output. Materials and Methods: We examined the effects of alginate content, biomass age, initial cell loading (ICL), bead size, and solidification duration in calcium chloride solution on enzyme synthesis. We conducted batch fermentations using both immobilized and free cells. Results: Alpha-amylase production significantly increased with the alginate concentration ratio, achieving a maximum enzyme yield of 23.5 U/mL at a 30 g/l alginate concentration, utilizing an initial cell loading of 1.5 g in 150-200 beads per flask. These involved cells from a 12-hour culture with a bead size of 5.0 mm, were solidified for 24 hours in a 2.5% (w/v) calcium chloride solution. The yield of the immobilized cells was approximately 111.71% higher than that of the free cells, which produced 11.1 U/ml. The immobilized cells consistently generated alpha-amylase over five repeated cycles, attaining a peak value of 23.5 U/ml during the first cycle, which was 2.2-fold more than the control (free cells). Conclusion: We used a basic mass balance analysis to understand the growth of both fractions and the dynamics of amylase production in free cells and cells immobilized in Ca-alginate beads. The production of alpha-amylase in immobilized cells results in enhanced volumetric activities during fermentation. Notable advantages of this technique encompass prolonged stability, reuse and recycling, and the potential for adaptable regeneration.